2001
DOI: 10.1080/07391102.2001.10506718
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Sialyloligosaccharide Fragments into the Active site of Influenza Virus N9 Neuraminidase

Abstract: Molecular modeling studies have been carried out to investigate the interactions between substrate sialyloligosaccharide (SOS) fragments bearing different glycosidic linkages and influenza virus N9 neuraminidase, a surface glycoprotein of influenza virus subtype N9. The studies revealed that the allowed orientation for sialic acid (SA) is less than 1% in the Eulerian space at the active site. The active site of this enzyme has enough space to accommodate various SOS fragments, NeuNAcalpha(2-3)Gal, NeuNAcalpha(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…To our knowledge, there are no available data on NA recognition of ␣2,9-linked sialic acids, which are typical of serogroup C capsules. However, molecular modeling studies showed that the active site of influenza virus N9 NA has enough space to accommodate substrates bearing the four types of glycosidic linkages (39). Whatever the serogroup, the exosialidase activity of the viral NA is unlikely to lead to a complete disruption of the capsule.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no available data on NA recognition of ␣2,9-linked sialic acids, which are typical of serogroup C capsules. However, molecular modeling studies showed that the active site of influenza virus N9 NA has enough space to accommodate substrates bearing the four types of glycosidic linkages (39). Whatever the serogroup, the exosialidase activity of the viral NA is unlikely to lead to a complete disruption of the capsule.…”
Section: Discussionmentioning
confidence: 99%